Education 3410. Comparative educational administration. Program 20 - Parsons, Llewellyn, 1930- (Teacher) (MUN Extension Service, 1979)
Levels of education and occupational plans of High School students in Newfoundland Overlay of another video's audio in the beginning. Video ends abruptly.